Annual Plan 1970-71 Budget-Plan Link Supplement to the Detailed Budget Estimates for 1970-71 Government of Tamil Nadu - Planning Commission (Planning Commission, 1970)
The Total presenting the plan expenditure for 1970-71 as now presented. The expenditure included in the Plan is only such expenditure as is needed for developmental activity over the level attained at the commencement of the Plan period. The expenditure on maintaining the levels of services started in the First, Second, Third Plans and the three Annual Plans is treated as committed expenditure and shown as non-Plan expenditure. Thus the outlay included in the Fourth Plan is over and above such committed expenditure.
Finance Department, Government of Tamil Nadu